Risk-Based Supplier Selection Using Integrated DEMATEL-ANP-RFMEA Approach in Street Lighting Pole Fabrication Industry - Harun Yudhistira Siswanto Putra; Suparno (Tekmapro, 2026)
Supplier selection in the Public Street Lighting (PJU) pole fabrication industry plays a strategic role in supporting the effectiveness of business processes and requires objective and structured decision-making. However, in practice, supplier selection is often conducted subjectively without adequate consideration of the interrelationships among criteria and supplier-related risks. This study proposes an integrated decision-making model combining the DEMATEL, ANP, and RFMEA methods to address these limitations. The DEMATEL method is employed to identify cause–effect relationships among selection criteria, while the ANP method is used to calculate priority weights by considering interdependencies within the decision network. Furthermore, the RFMEA method is applied to evaluate supplier risks based on Likelihood, Impact, and Detection values, and the resulting Risk Priority Number (RPN) is incorporated into the risk management criterion of the ANP model. The proposed model generates a ranked list of suppliers and provides a systematic, objective, and risk-based framework for supplier selection in the PJU pole fabrication industry.